Respuesta :

Answer:

2x - 10 = 44 + 8x

7x - 4 = 20 =3x

2(x-3) = -20

15 - 4x + 5 = 32

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    2*x-10-(44+8*x)=0

Pull out like factors :

  -6x - 54  =   -6 • (x + 9)

  -6   =  0

 Solve  :    x+9 = 0

Subtract  9  from both sides of the equation :

                     x = -9

x = -9

Move all terms containing

x

to the left side of the equation.

4

x

4

=

20

Move all terms not containing

x

to the right side of the equation.

4

x

=

24

divide each term by 4

x = 6

2(x−3)=−20

Step 1: Simplify both sides of the equation.

2(x−3)=−20

2x−6=−20

Step 2: Add 6 to both sides.

2x−6+6=−20+6

2x=−14

Step 3: Divide both sides by 2.

2x

2

=

−14

2

x=−7

−4x+20=32

Step 2: Subtract 20 from both sides.

−4x+20−20=32−20

−4x=12

Step 3: Divide both sides by -4.

−4x

−4

=

12

−4

x=−3